2019
DOI: 10.18502/ijrm.v17i12.5793
|View full text |Cite
|
Sign up to set email alerts
|

Frozen embryo transfer: Endometrial preparation by letrozole versus hormone replacement cycle: A randomized clinical trial

Abstract: Background: The endometrial preparation with stimulating natural cycles for frozen embryo transfer (FET) have benefits like lower cost and ease of use. Objective: Comparing the clinical outcome of letrozole versus hormone replacement (HR) for endometrial preparation in women with normal menstrual cycles for FET in artificial reproduction techniques. Materials and Methods: A total of 167 participants who had frozen embryos and regular ovulatory cycles were randomly divided into two groups for endome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Although there are many options for the preparation of the endometrium, there is still no uniform recommendation for the preparation of the FET endometrium for different groups of women to date (6)(7)(8). For patients with abnormal ovulation in particular, there have been few studies on FET protocols; notably, most of these studies focus only on the clinical pregnancy rate or LBR (9)(10)(11) and pay little attention to the regimen's safety for offspring. The most frequently used regimens for patients with abnormal ovulation are ovulation induction by letrozole and HRT.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are many options for the preparation of the endometrium, there is still no uniform recommendation for the preparation of the FET endometrium for different groups of women to date (6)(7)(8). For patients with abnormal ovulation in particular, there have been few studies on FET protocols; notably, most of these studies focus only on the clinical pregnancy rate or LBR (9)(10)(11) and pay little attention to the regimen's safety for offspring. The most frequently used regimens for patients with abnormal ovulation are ovulation induction by letrozole and HRT.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al also demonstrated increased LBR in L-FET group when compared to AC-FET group in women with polycystic ovary syndrome in a retrospective study [29]. And lastly, CPR was significantly higher and E2 levels on ET day were significantly lower in L-FET group versus AC-FET group in a prospective randomized study in patients with normal menses [49]. In accordance with these studies, we demonstrated statistically significantly improved IR, CPR, LBR with a lower peak E2 levels and cancellation rates in L-FET cycles.…”
Section: Discussionmentioning
confidence: 87%
“…The frozen–thawed ET and progesterone supplementation were done according to protocols reported in previous study 14 . Briefly, frozen embryos were transferred into the uterine cavity via the using sterile ET catheter under trans‐abdominal ultrasound guidance when the desired endometrial thickness has been achieved (7–9 mm).…”
Section: Methodsmentioning
confidence: 99%